The transformation of the Afar commons in Ethiopia: State coercion, diversification and property rights change among pastoralists - Hundie, Bekele; Padmanabhan, Martina Aruna (International Food Policy Research Institute, 2008)
The major economic activity for pastoralists is animal husbandry. The harsh environment in which herders raise their livestock requires constant mobility to regulate resource utilisation via a common property regime. In contrast to the mobile way of life characterizing pastoralism, agriculture as a sedentary activity is only marginally present in the lowlands of the Afar regional state in Ethiopia. Nevertheless, this study reveals a situation where the traditional land-use arrangements in Afar are being transformed due to the introduction of farming. In the past, the Imperial and the Socialist governments introduced large-scale agriculture in a coercive manner, thereby instigating massive resistance from the pastoralists. Currently, the recurrence of drought in the study areas has facilitated the subdivision of the communal land on a voluntary basis for the purpose of farming. Qualitative and quantitative analysis highlight the drivers, both coercive and non-coercive, of the transformation of traditional property rights of Afar pastoralists.